Communication Strategy Of Posyandu (Family Empowerment And Welfare) In Conveying Health Message To Community (A Case Study of Immunization Benefit Messages by Posyandu (Integrated Service Post) In Katulampa Village) (Lembaga Penelitian dan Pengabdian Nasyarakat Universitas Pakuan, 2017)
This research is located in Katulampa, East Bogor District, Bogor City, West Java Province and has an area of 491 Ha. Regency of Cimahpar in the north, Regency of Tajur in the south, Regency of Baranangsiang in the west and Sukaraja Village in the east, Bogor Regency.Katulampa urban altitude is located at 500 meters above sea level and has a temperature and an average of 36 degrees Celsius (Katulampa Urban: 2011). The distribution of Katulampa Urban Village consists of 20 Rukun Warga (RW) (hamlets) and 107 Rukun Tetangga (RT). Posyandu is a program of the Ministry of Health which in its implementation cooperate with Posyandu. Before a program is socialized to the community, careful planning is made. In the planning of culture and social life and local wisdom in a region becomes important capital in the successful implementation of the program. The message to be conveyed should be able to reach as many people as possible (communicant). Communities targeted by messages are heterogeneous. After considering and discussing and reaching an agreement, the message from the center will be rolled into the ranks below, in this case to the provincial, municipality, district, administrative Village, RW and RT levels. The message was then restored in a more conical way by involving the Provincial Health Office and the community consisting of Posyandu Chairman, Posyandu Cadre and health workers. Mothers who have been informed about the benefits of immunization deliver it to the husband, who will usually decide whether the child should be immunized or not. Most husbands are already aware of the benefits of immunization for the health of infants and toddlers ages 0 months to five years. Posyandu cadres adapt to targeted community conditions. The prevailing culture in society is an important consideration in the persuasive of parents who have babies and toddlers.The communication strategy includes macro strategy (planned multi media strategy) and micro (single communication medium strategy).